Association of Interleukin-1α Functional Polymorphism with Risk of Chronic Periodontitis in Han Chinese Population - She, Xiaowei (Genet Res (Camb), 2021)
Chronic periodontitis (CP) is a common inflammatory illness affecting a large proportion of humans. Genetic factors are thought to play important roles in its onset and development. A functional polymorphism (rs1800587) in the promoter of the interleukin-1α gene (−889 C/T) has been found to confer risk of CP primarily in Europeans, but the association between this variant and CP in the Chinese population remains less conclusive. In the current study, we aimed to investigate the association between rs1800587 and CP in case-control samples of Han Chinese origin. A total of 1,777 study subjects, including 884 CP patients and 893 healthy controls, were collected. Genotyping of rs1800587 was performed using the SNAPSHOT method, and statistical analyses were conducted to evaluate the association between rs1800587 and CP. In our sample, rs1800587 was significantly associated with the onset of CP (additive model, T-allele vs. C-allele, p = 0.00359, odds ratio = 1.446, 95% confidence intervals (CIs) = 1.127–1.855; dominant model, (TT + TC) vs. CC, p = 0.00250, odds ratio = 1.502, 95% CIs = 1.152–1.957; overdominant model, TC vs. (TT + CC), p = 0.00264, odds ratio = 1.508, 95% CIs = 1.152–1.976). The T-allele and [TC] genotypes of rs1800587 were significantly overrepresented in CP patients compared with controls. Our data suggest that rs1800587 of IL-1α is significantly associated with the risk of CP in Han Chinese subjects, further confirming its possible involvement in the disease.